2018
DOI: 10.2217/fon-2018-0671
|View full text |Cite
|
Sign up to set email alerts
|

Stage III Melanoma Incidence and Impact of Transitioning to the 8th AJCC Staging System: A US Population-Based Study

Abstract: Aim: To estimate incidence of stage III melanoma using the American Joint Committee on Cancer (AJCC) staging, 7th and 8th edition. Patients & methods: The SEER US cancer registry was analyzed (2010–2014). AJCC7 stages were recorded in the data; AJCC8 stages were inferred. Results: Of 106,195 melanoma patients, 7669 and 7342 had stage III melanoma by AJCC7 and AJCC8, respectively (95% overlap). Nearly 30% of patients with AJCC7 stage III melanoma were reclassified in a higher stage III group by AJCC8 versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Another US study which assessed incidence rates in the SEER program, showed an increase in the stage III incidence rate between 2010 and 2014 from 1.21 to 1.48 per 100,000 persons/year (based on American Joint Committee on Cancer [AJCC] 7th edition staging criteria; Table 1). Similar rates were observed when AJCC 8th edition staging criteria was used (2010, n = 1.23 per 100,000 persons/year; 2014, n = 1.47 per 100,000 persons/year) [12]. The statistical significance of this increase was not reported.…”
Section: Incidence Rates In Stages II and Iii Melanomasupporting
confidence: 57%
See 3 more Smart Citations
“…Another US study which assessed incidence rates in the SEER program, showed an increase in the stage III incidence rate between 2010 and 2014 from 1.21 to 1.48 per 100,000 persons/year (based on American Joint Committee on Cancer [AJCC] 7th edition staging criteria; Table 1). Similar rates were observed when AJCC 8th edition staging criteria was used (2010, n = 1.23 per 100,000 persons/year; 2014, n = 1.47 per 100,000 persons/year) [12]. The statistical significance of this increase was not reported.…”
Section: Incidence Rates In Stages II and Iii Melanomasupporting
confidence: 57%
“…A single Swedish study reported age-adjusted incidence rates for the stage II melanoma population [13]. Unadjusted incidence rates for stages II and III melanoma populations were reported in two studies from the USA (Table 1) [11,12].…”
Section: Characteristics Of Included Incidence Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent updates to the American Joint Committee on Cancer (AJCC) staging guidelines highlight the clinical need for adjuvant therapies in melanoma [34]. Sentinel node staging has become mandatory in the most recent AJCC guidelines, which means fewer patients are being diagnosed with stage I/II disease and more with stage III disease [35]. Because of this, we know more patients have micrometastatic disease.…”
Section: Adjuvant Versus Neoadjuvant Therapymentioning
confidence: 99%